ANALISIS PERWATAKAN TOKOH DALAM NOVEL PERTEMUAN DUA HATI KARYA NH. DINI - Maria Intan Purnama Giawa; Agustinus Duha; Sridelli Dakhi (Universitas Nias Raya, 2022)
This research is motivated by the uniqueness of the novel story that makes researchers interested in knowing the character of the characters contained in the novel Meeting Two Hearts by Nh. Dini. The purpose of this research is to identify the character or character of the protagonist, antagonist, and tritagonist as well as to describe the analytical and dramatic depiction of the character or character of the protagonist, antagonist, and tritagonist in the novel Meeting Dua Hati Karya Nh. Dini. The method used in this research is a descriptive qualitative approach. The research findings show that the character of Bu Suci in the novel Meeting Two Hearts is the protagonist, while the character of Waskito is the antagonist. And the tritagonist character is played by Grandma Waskito. The character's character is described by the author analytically and dramatically. It can be concluded that Bu Suci has a protagonist character or character, which is often relentless, easily moved or affectionate, kind, helpful, and caring, while Waskito has an antagonistic character or character, namely nosy, mischievous, annoying, evil, rude, likes hitting, ruthless, cruel, angry, rebellious, mischievous, always argues and refutes advice, never wants to be asked, is rude, and lies. The novel of Meeting Two Hearts is very good as reading material and as a reference for teaching materials, because the novel contains many positive and good life values ​​if used as experiences and examples. Based on the results of this study, it is suggested that this research can be used as reading material and as a reference for teaching materials.